A survey on factors influencing people to choose their career - Omar, Muhamad Fuzi; Othman, Muhammad Hanif; Mohideen, Ume Salamah; Zainudin, Farah Amira; Md Saleh, Nor Farhana; Shamsul Akmar, NurAmalina (ijcas.net, 2016)
The objectives of the study are to identify and rank the factors that influence people to choose the career and to discover the relationship between demographic variables with factors that influencing people in choosing career. The data are collected using survey questionnaires. This study is conducted by focusing on different ethnicity between Malay, Chinese and Indian. The number of respondents is 156 respondents. The methodologies used are descriptive statistics, factor analysis and non-parametric techniques using Kruskal-Wallis test. The results from factor analysis show four new factors which influence people’s career. Those factors are being labelled as 1) salary and rewards, 2) lifestyles, 3) interest and 4) qualifications